(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Khitrova A. V. Realization of technologies of civil education of students in a educate process in higher education. The article reveals the essence of technology and content of civic education of students in the educational process in higher education. The key stages and directions activity of subjects of higher school are certain. The examples of the use of forms and methods of forming of civic of students are resulted.